PENGARUH LIKUIDITAS DAN LEVERAGE TERHADAP PROFITABILITAS DAN NILAI PERUSAHAAN PADA PERUSAHAAN-PERUSAHAAN IDXTECHNO PERIODE 2017-2019 - Setyawan, Dendy (JEA17: Jurnal Ekonomi Akuntansi, 2021)
This study was conducted to examine the effect of Liquidity and Leverage on Profitability and Firm Value of Companies listed at IDXTECHNO for the 2017-2019 period. Secondary data is obtained from the company's financial statements uploaded on the IDX's official website and the company's official website. The data used were selected based on the similarity of the available annual report data. The analysis method uses quantitative analysis methods using the SmartPLS 3.0 program. The results showed that the Liquidity and Leverage variables did not have an effect on the Profitability variable, but the Liquidity variable had a significant influence on the Firm Value variable, while the Leverage variable had no effect on the Firm Value variable. While the Profitability variable has a significant influence on the Firm Value variable.